The Privileges of the Council of Rectors (Observatorio Económico, 2010)
Why is a large share of the public resources allocated to higher education handed to a body that exists on the basis of history and privilege rather than on the merits of its members? The government announced reforms to higher education. Although the details of the proposals are not yet known, the Minister of Education and the head of the Ministry's Higher Education Division announced reforms along at least three lines. Continue reading...
Keywords: Council of Rectors; higher education; CRUCH; MINEDUC